PENGARUH KEPEMIMPINAN, BUDAYA ORGANISASI DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI DI BADAN KEPEGAWAIAN DAERAH KABUPATEN LABUHANBATU SELATAN - Muhammad Robiq Muhazir; Waldy Depuansyah Harahap; Muhammad Zul Indra; Norman Hadiyanto; Fakhrurrazi Salim (Manajemen dan Bisnis, 2021)
Problem of this study how influence of leadership on performance. How influence of    organization culture on performance. How influence of  job dicipline on  performance. How influence leadership,    organization culture and  job dicipline on   performance. The purpose of this study to determine and analyze the effect of  leadership on   performance. Determine and analyze the effect of   organization culture on   performance. Determine and analyze the effect of  job dicipline on   performance. Determine and analyze the effect of  leadership,  organization culture and  job dicipline on   performance.  Sample in the study is 34 employees. Data analysis techniques used in this study is descriptive analyze and multiple linear regression analysis. The results of the study indicate leadership variable has a positive and significant effect on performance.  organization culture variable has a positive and significant effect on   performance.  job dicipline variable has a positive and significant effect on performance. Leadership,  organization culture and  job dicipline variable has a positive and significant effect on   performance.